(3JgPjH GdeQTO aj Gdhba hGdGHJOGAs - (3eLghds ((3CMeO Hf SYO GdOjf GdSdhjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdeaJJM cdGeg HMeOg GdeLQj GdCdSfI Hg daXG ef YfOg GdeSJfWb ebGhd GdfcQ Ydi MhGgd fcOg hYdi Bdg fbdI GdbQBf hMedI hOGjY GdOjf ef MQGS eUGMa GdJfRjd hShGS eOGQL Gdhbha heNGQL GdMQha Yf GdJMQja HGdJYdjes
(3BNQgG (B:s
(3CHI MGJe hCHh HcQ hGdCNaT dG jbahf Edi BNQ GdShQI dGfg Ydjg GdSdGe CeQ Gf jbhd LejY GdcdeGJ aj LhGH hGMO dHjGf CeQ hGMO hdG hba aj GdeYhPJjf Edi BNQgG dUMI GdYWa hGJSGb GdcdeGJ HYVgG Ydi HYV aj ebhd hGMO hHGddg GdJhajb hbO Je Gdhbhas
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs